Confidence reports in decision-making with multiple alternatives violate the Bayesian confidence hypothesis - Hsin-Hung Li (Nature Portfolio, 2020)
Conventional theory suggests that people’s confidence about a decision reflects their subjective probability that the decision was correct. By studying decisions with multiple alternatives, the authors show that confidence reports instead reflect the difference in probabilities between the chosen and the next-best alternative.